2011
DOI: 10.1007/s00592-011-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone decreases fasting plasma peptide YY3–36 in type 2 diabetic women: a possible role in weight gain?

Abstract: Rosiglitazone often results in weight gain. We hypothesized that rosiglitazone may modulate circulating levels of ghrelin and peptide YY(3-36) and this modulation may be related to weight-gaining effect of this agent. This study was designed as an open-label, randomized, controlled trial of 3-month duration. Women with newly diagnosed type 2 diabetes were studied. Twenty-eight of the 55 eligible participants were randomly assigned to receive rosiglitazone (4 mg/d). Twenty-seven patients with diabetes matched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…TZD-induced weight gain is attributable to increased subcutaneous fat depots due to body fat accumulation and redistribution, and body fluid retention [161]. Furthermore, in one clinical study, individuals given rosiglitazone had lower fasting plasma peptide YY and experienced increased hunger [162]. Such an inhibitory effect on peptide YY, which is an appetite suppressor, may also partly explain TZD-induced weight gain.…”
Section: Obesitymentioning
confidence: 99%
“…TZD-induced weight gain is attributable to increased subcutaneous fat depots due to body fat accumulation and redistribution, and body fluid retention [161]. Furthermore, in one clinical study, individuals given rosiglitazone had lower fasting plasma peptide YY and experienced increased hunger [162]. Such an inhibitory effect on peptide YY, which is an appetite suppressor, may also partly explain TZD-induced weight gain.…”
Section: Obesitymentioning
confidence: 99%
“…Peripheral edema and excessive weight gain are known adverse effects of rosiglitazone as well as other thiazolidinediones (1418). However, peripheral edema occurred in only 1.7% of participants in the M + R group, which was not significantly more than in the other two groups and compares favorably to the 4–6% occurrence of edema in similar trials of adults (17,18). In addition, using the protocol-defined AE criteria set a priori (>10% increase in BMI between visits), excessive weight gain occurred in 9.0% of the M + R group compared with 4.3 and 7.3% in the M and M + L groups, respectively (not statistically significant).…”
Section: Discussionmentioning
confidence: 50%
“…The apparent contradiction between equivalent incidence of excessive weight gain between 3-month visits across treatment and significantly higher BMI across 60 months in the M + R group can be explained by the specificity of the study’s definition of excessive weight gain as an AE, which was designed primarily to provide an early signal of safety concerns. Studies of overweight adults treated with rosiglitazone have shown a gain in BMI ranging from 1.1 kg/m 2 after 12 weeks (17) to 0.35 after 24 weeks (15), which compares to about 0.4 at 12 weeks and 0.7 at 24 weeks among participants in TODAY’s M + R group (6). Weight gain from rosiglitazone seems to be a potential problem in children and adolescents, as it is in adults.…”
Section: Discussionmentioning
confidence: 99%